Powódź – wilgotne zabija suche. Klęska męskości w Drachu Szczepana Twardocha - Imiela, Paulina (Śląskie Studia Polonistyczne, 2020)
In the article the author presents her interpretation of corporeality in Szczepan Twardoch’s books. She performs her analysis of male body’s image by emphasizing the opposition between biology-based disruptions of social constructs and machine-like process yielding the projection of a perfect soldier. What was indicated by the author is the influence of German authors on Twardoch’s novels, particularly Klaus Theweleit’s works. The analysis focuses on Josef Magnor, the main character of Twardoch’s Drach, serving as a figure of defeat in the context of variegated social relations, most of all relating to masculinity. The key to understand the failure of masculinity in Twardoch’s works seems to be the opposition: the dry – the wet, which facilitates transferring of considerations on war symbols directly into interpretation of Polish recent literature.